L’Entreprise-agence de Jean Walter. 1918-1957. L’architecture au service de l’affairisme ? - Marie Gaimard (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
In a context of progressive regulation of the architectural profession in France throughout the first half of the 20th century, Jean Walter’s career testifies to the liberties taken by some professionals before the enactment of the loi du 31 décembre 1940, as he seemingly ignored any of the deontological debates taking place in the profession. Having received some recognition at the beginning of the 1930s, Jean Walter was nevertheless ostracized in 1935 and remained so throughout most of his career, due to financial-political scandals in which he was involved. The critical fortune of his achievements in the historiography of architecture has, however, left its mark up until today. Towards the end of his life, his name appeared in popular newspapers, as well as architectural reviews. Imbued with liberalism and inspired by the industrial world, he transposed into the architectural world methods originating from the scientific organization of work, sometimes literally. This article outlines the opportunistic view that Jean Walter maintained, questioning its implementation.